Comparative Feasibility of Shifting Cultivation and Direct Seed System Rice Farming in Yaba Maru Village, Tanah Miring District, Merauke Regency, South Papua Province - Sutarman Sutarman; Nina Maksimiliana Ginting; Ineke Nursih Widyantari (Universitas Muhammadiyah Palembang, 2024)
The research objective was to compare production costs, revenue, income, and farm feasibility using the transplanting system method (tapin, a traditional method of planting rice seedlings) and direct seed planting system (tabela, a modern method of planting rice seeds directly into the field) in Yaba Maru Village, Tanah Miring District. The research location was chosen purposively by considering Yaba Maru Village as a rice center. The research population was 611 farmers, and the number of research samples was 80 farmers consisting of 40 tapin farmers and 40 tabela farmers. The data used in the study were primary data from observation, documentation, and questionnaires, as well as secondary data from BPS, village heads, literature, and the internet. The data analysis method used quantitative descriptive analysis. The results showed that the average total cost incurred by the Tapin system was higher than that of the Tabela system. The tapin system cost was Rp 15,714,237, consisting of fixed costs of Rp 3,378,353 and variable costs of Rp 12,335,884, and the tabela system was Rp 13,989,800 consisting of fixed costs of Rp 3,667,588, and variable costs of Rp 10,322,213. Farming receipts for the tapin system are higher than those for the tabela system, at Rp 29,061,450 for tapin and Rp 26,670,600 for tabela. The income received by the tapin system rice farming is higher than the tabela system, namely 13,347,213 for tapin and Rp 12,680,800 for tabela. The farm feasibility value of the tabela system is higher than the tapin system, with an R/C ratio of 1.91 for the tabela system and 1.85 for the tapin system.